Adomian decomposition method for two-dimensional nonlinear fredholm integral equation of the second kind - Wan Mohammad Ayub, Wan Seri Nurulhuda (2013)
Nonlinear phenomena’s that appear in many applications in science fields such as fluid dynamic, plasma physics, mathematical biology and chemical kinetics can be modeled by integral equation. Nonlinear integral equation usually produces a considerable amount of difficulties. This problem can be handling with some method such as Adomian decomposition method (ADM) and modified Adomian decomposition method (MADM). In this research, ADM and MADM are applied to solve two-dimensional nonlinear Fredholm integral equation of the second kind (FIE). We used ADM to find the exact solution and MADM to find the numerical approximation. From the observation with some example are presented in this research, the first five terms convergent numerical approximations give the good approximation.